PENGGUNAAN RESPONSE SURFACE METHODOLOGY (RSM) PADA OPTIMASI KADAR NITROGEN DAN FOSFOR DALAM KULTUR DUNALIELLA SP. SEBAGAI SUMBER ALTERNATIF LIPID - Ramdhani Supriatna, Mohamad
Dunaliella sp. has the potential to be a sustainable alternative source of lipids due to its rapid growth rate, ability to adapt to variety of environmental conditions, and does not require productive land. Nutrient limitations, especially N and P limitations, can increase lipid accumulation in Dunaliella sp., but this stress can inhibit microalgae growth, thus nutrition optimization is required to maximize lipid accumulation and accommodate microalgae growth. This research was conducted to determine the optimum N and P levels to increase lipid accumulation in Dunaliella sp. Dunaliella sp. cultivation was done by using Walne medium for 9 days with variations in N and P levels in the range of 0.346—2.014 mM and 0.035—0.205 mM. The measurement of Dunaliella sp. growth was done every day based on the dry weight of the biomass. Lipid analysis was performed on day 9 following the Bligh & Dyer method. Measurement of nitrate and phosphate consumption was carried out using spectrophotometric method. Fatty acid profile analysis was performed by GC-MS (gas chromatography-mass spectrometry). Determination of growth models, consumption of nitrate and phosphate were conducted using a logistic modeling approach. Optimum N and P levels to obtain high lipid accumulation were carried out by response surface methodology (RSM) analysis. Results in this study indicated that, the highest biomass was obtained at N/P levels of 1.18/0.035 mM which reached 1.28 ± 0.24 g/L, the highest lipid accumulation was obtained at N/P levels of 0.59/0.18 mM reaching 67.12±1.78 mg/g dry weight. The results of the analysis showed that the fatty acids contained in the lipids of Dunaliella sp. include palmitic acid, stearic acid, linoleic acid, and oleic acid. Logistic modeling can model the growth of Dunaliella sp. well (R2 > 0.9). Response surface methodology (RSM) analysis gave optimum N and P levels for lipid accumulation, namely 0.67 mM and 0.035 mM with biomass concentration of 0.99 ± 0.02 g/L and lipid yield of 63.10 ± 19.53 mg/g .